Mobile Banking Adoption and Service Quality of Commercial Banks: A Case Study of Stanbic Bank- Mbarara Branch. - Ritah Nabaasa (Uganda Christian University, 2023)
The study established the effects of mobile banking adoption on service quality of commercial banks: a case study of Stanbic Bank- Mbarara Branch. It specifically focused on; understanding how the perceived ease of use of mobile banking adoption affects service quality, finding out how the perceived usefulness of mobile banking adoption influences service quality and establishing the relationship between the social influence of use of mobile banking adoption and service quality in Stanbic Bank-Mbarara. The study was carried out using a cross sectional survey research design where both quantitative and qualitative research approaches were also used. The data was collected using questionnaires and interviews during the data collection, both purposive and simple random sampling methods were used. A sample size of 44 respondents who are management and employees from Stanbic Bank, Mbarara branch was also used in the study. From the findings, it was revealed that the perceived ease of use and usefulness of mobile banking adoption were found to play significant roles in enhancing service quality, as respondents expressed ease in learning and navigating the mobile banking platform, and acknowledged its contribution to efficiency and customer convenience. Moreover, the study highlighted the importance of social influence within the bank, as colleagues' positive experiences and recommendations were found to motivate and comfort users, ultimately contributing to improved service quality. These findings underscore the importance of not only providing user-friendly mobile banking services but also fostering a supportive and influential social environment to maximize service quality in the banking sector. Finally, the study recommends that Stanbic Bank-Mbarara should focus on enhancing the user experience by updating the mobile banking interface and providing comprehensive training. They should also continually improve the efficiency and convenience of the service by seeking customer feedback and introducing new features. Fostering a culture of social influence within the organization, recognizing and rewarding employees who promote mobile banking and monitoring service quality through customer feedback are also vital.
This is a dissertation.